22nd International Conference on Human-Computer Interaction With Mobile Devices and Services 2020
DOI: 10.1145/3379503.3403553
|View full text |Cite
|
Sign up to set email alerts
|

Messaging Beyond Texts with Real-time Image Suggestions

Abstract: While people primarily communicate with text in mobile chat applications, they are increasingly using visual elements such as images, emojis, and memes. Using such visual elements could help users communicate clearly and make chatting experience enjoyable. However, finding and inserting contextually appropriate images during the chat can be both tedious and distracting. We introduce Milli-Cat, a real-time image suggestion system that recommends images that match the chat content within a mobile chat applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…High privacy cost. We observed that one app (i.e., Phishing Eyes) sends users' incoming/outgoing call numbers, SMS texts, voice calls, or installed app lists to its server, each of which is privacy-sensitive information [21,72,73]. We believe that the existing approach of sending privacy-sensitive information demands a high privacy cost, rendering this approach impractical.…”
Section: Existing Defense Appsmentioning
confidence: 99%
“…High privacy cost. We observed that one app (i.e., Phishing Eyes) sends users' incoming/outgoing call numbers, SMS texts, voice calls, or installed app lists to its server, each of which is privacy-sensitive information [21,72,73]. We believe that the existing approach of sending privacy-sensitive information demands a high privacy cost, rendering this approach impractical.…”
Section: Existing Defense Appsmentioning
confidence: 99%